Reframing human trafficking awareness campaigns in the United States: goals, audience, and content - Savoia, Elena; Piltch-Loeb, Rachael; Muibu, Daisy; Leffler, Amy; Hughes, Diana; Montrond, Alberto (Frontiers in Public Health, 2023)
Introduction: Human trafficking (HT) awareness campaigns can educate the public and specific professional figures about this crime and ways to prevent it. However, there currently remains a gap in terms of how to best frame such campaigns without stigmatizing groups of individuals or portraying victims in unrealistic ways.We conducted four focus groups with 22 experts in HT to explore their perspectives and opinions on current challenges in the framing of HT awareness campaigns in the United States. Focus groups were conducted via Zoom and transcribed verbatim. Two independent reviewers analyzed the transcripts to identify themes using an inductive approach. The results of the focus groups analysis were used to structure the guiding questions of a brainstorming technique named Nominal Group Technique (NGT). Fifteen of 22 experts that participated in the focus groups joined the in-person NGT with the intent of generating ideas and achieving consensus on target audiences, goals, and content of human trafficking awareness campaigns. At the end of the NGT participants ranked priority for actions in the development of HT awareness efforts in the United States.Results: During the NGT the experts provided a number of recommendations to improve HT awareness and to empower victims to reach for help. They pointed to the need for: awareness efforts that describe HT on a spectrum of human abuse and exploitation; training for professional figures about trauma-informed care and communication; and efforts that empower trafficked victims to seek support. They also pointed to the need to develop awareness efforts tailored to local needs in close collaborations with the community-based organizations that can champion their dissemination and be the primary point of access for victims seeking help.